Hubungan Kemampuan Komunikasi Interpersonal dan Penggunaan Sumber Belajar Digital dengan Motivasi Belajar Siswa pada Mata Pelajaran Ekonomi di SMA Negeri 2 Sukoharjo - Helmiyah Tsabita; Soetarno Joyoatmojo; Almh. Kristiani (Journal on Education, 2023)
The purpose of this research is to test 1) the relationship between interpersonal communication skills and students' learning motivation in economics subjects at SMA Negeri 2 Sukoharjo; 2) the relationship between the use of digital learning resources and students' learning motivation in economics subjects at SMA Negeri 2 Sukoharjo; 3) the relationship between interpersonal communication skills and the use of digital learning resources with students' learning motivation in economics subjects at SMA Negeri 2 Sukoharjo. The research method used was quantitative with a population of class X students at SMA Negeri 2 Sukoharjo. The sampling technique used Simple Random Sampling with a sample size of 125 respondents. Data collection uses a questionnaire. The data validity test in this study used the product moment correlation test, while the reliability test used the Cronbach's Alpha method.